Seleção de progênies de cafeeiro visando a resistência durável à ferrugem e características agronômicas - Dias, Rafael Antônio Almeida (2016)
This study had the objective of selecting coffee progenies aiming at advancing the selection for obtaining cultivars resistant to coffee rust and with agronomic traits superior to traditional cultivars. The experiment was installed at the EPAMIG experimental field in Patrocinio, Minas Gerais, Brazil, consisting of 25 progenies derived from the cross between cultivars from the Icatu and genetic materials from groups Catuai Amarelo IAC 62 and IAC 17, Catuai Vermelho IAC 99, Rubi and segregating progenies originated from the retrocrossing of Catuai with Mundo Novo, identified as IAC 5002 and IAC 5010, as well as a cross between Acaia and Catuai Amarelo IAC 17. We used as witness two progenies in advanced generation, promising for the resistance to rust, origina ted from the cross between Catimor and Icatu groups, which resulted in cultivar Aranas. The progenies meet in generation F3 and were obtained by the coffee Breeding Program conducted in Minas Gerais, Brazil, and coordinated by EPAMIG, with the collaboration of the Universidade Federal de Viçosa (UFV) and Universidade Federal de Lavras (UFLA). We used a randomized blocks design, with three replicates, totalizing 75 plots, with 10 plants each. The spacing used was of 3.5 m between lines and 0.8 m between plants. We evaluated characteristics: productivity in processed coffee bags ha-1, plant vigor, percentage of grains retained in sieve 17 and above, sieve 10 and bottom, adopting the mixed linear model analysis. For rust incidence and severity we performed analysis of variance, comparing the means by the Scott Knott test at 5% of significance when presenting significant difference. We also conducted selection gain estimates by means of direct selection for each trait when compared with the sum of positions. Progenies 13 (Icatu V. IAC 4040 x IAC 5002), and progeny 3 (Icatu A. IAC 2944 x IAC 5002), were promising for the generation advancement, for positioning among the five most productive progenies. the five progenies selected by the sum of positions, and the progenies presenting lower rust incidence. The selection gain obtained with the direct selection was superior to the gains obtained by the sum of the positions.